Non-additive Effects in Genomic Selection - Varona, Luis; Legarra, Andres; Toro, Miguel A.; Vitezica, Zulma G. (Frontiers in Genetics, 2018)
In the last decade, genomic selection has become a standard in the genetic evaluation of livestock populations. However, most procedures for the implementation of genomic selection only consider the additive effects associated with SNP (Single Nucleotide Polymorphism) markers used to calculate the prediction of the breeding values of candidates for selection. Nevertheless, the availability of estimates of non-additive effects is of interest because: i) they contribute to an increase in the accuracy of the prediction of breeding values and the genetic response; ii) they allow the definition of mate allocation procedures between candidates for selection; and iii) they can be used to enhance non-additive genetic variation through the definition of appropriate crossbreeding or purebred breeding schemes. This study presents a review of methods for the incorporation of non-additive genetic effects into genomic selection procedures and their potential applications in the prediction of future performance, mate allocation, crossbreeding and purebred selection. The work concludes with a brief outline of some ideas for future lines of that may help the standard inclusion of non-additive effects in genomic selection.